Integrated Myofibrillar Protein Synthesis in Recovery From Unaccustomed and Accustomed Resistance Exercise With and Without Multi-ingredient Supplementation in Overweight Older Men - Bell, Kirsten E.; Brook, Matthew S.; Snijders, Tim; Kumbhare, Dinesh; Parise, Gianni; Smith, Ken; Atherton, Philip J.; Phillips, Stuart M. (Frontiers in Nutrition, 2019)
Background: We previously showed that daily consumption of a multi-ingredient nutritional supplement increased lean mass in older men, but did not enhance lean tissue gains during a high-intensity interval training (HIIT) plus resistance exercise training (RET) program. Here, we aimed to determine whether these divergent observations aligned with the myofibrillar protein synthesis (MyoPS) response to acute unaccustomed and accustomed resistance exercise . Methods: A sub-sample of our participants were randomly allocated (n=15; age: 72 ± 7 years; BMI: 26.9 ± 3.1 kg/m2 [mean ± SD]) to ingest an experimental supplement (SUPP, n = 8: containing whey protein, creatine, vitamin D, and n-3 PUFA) or control beverage (CON, n = 7: 22 g maltodextrin) twice per day for 21 weeks. After 7 weeks of consuming the beverage alone (Phase 1: SUPP/CON only), subjects completed 12 weeks of RET (twice per week) + HIIT (once per week) (Phase 2: SUPP/CON + EX). Orally administered deuterated water was used to measure integrated rates of MyoPS over 48 h following a single session of resistance exercise pre- (unaccustomed) and post-training (accustomed). Results: Following an acute bout of accustomed resistance exercise, 0-24 h MyoPS was 30% higher than rest in the SUPP group (effect size: 0.86); however, in the CON group, 0-24 h MyoPS was 0% higher than rest (effect size: 0.04). Nonetheless, no within or between group changes in MyoPS were statistically significant. When collapsed across group, rates of MyoPS in recovery from acute unaccustomed resistance exercise were positively correlated with training-induced gains in whole body lean mass (r = 0.63, p = 0.01). Conclusion: There were no significant between-group differences in MyoPS pre- or post-training. Integrated rates of MyoPS post-acute exercise in the untrained state were positively correlated with training-induced gains in whole body lean mass. Our finding that supplementation did not alter 0-48 h MyoPS following 12 weeks of training suggests a possible adaptive response to longer-term increased protein intake and warrants further investigation. This study was registered at ClinicalTrials.gov as NCT02281331.